HELP PLEASE HELP @KONRAD1. The weight of a newborn baby chicken weighs 3-2 pounds. If an adult chicken can weigh up to 34 times more than a newborn chicken, how much does an adult chicken weigh? Leave your answer in the form ab.

Answers

Answer 1
Answer: the answer is 64 or 102 2 times 34 equals 64 and 3 times 34 equals 102

Related Questions

How do you set up the equation?
7. Mr. Garcia bought 27 large boxes of chlorine tablets and 33 small boxes of chlorine tablets. Eachlarge box cost $53 and each small box cost $32. How much did Mr. Garcia spend altogether?$2,487© $2,427® $2,5860 $1,431
What is 1/3 times 3x
What are the partial products of 42 x 5
A soccer team scored 2 goals in the first half. If they won the game by a score of 2 goals to 1 goal, how many goals did they score in the second half. Commutative property, Associative property, or Identity prorerty

What is the purpose of using fraction strips and a 1srip

Answers

the one strip is a whole fraction strip and the others are just part of the whole

If the quadratic equation x^2 + 18x +74=0 is rewritten in the form (x-p)^2 = Q what is the value of Q?A) -155

B) -74

C) 7

D) 9

Answers

If the quadratic equation x^2 + 18x +74=0 is rewritten in the form (x-p)²= Q. Then the value of Q is 7.

What is a quadratic equation?

It is a polynomial that is equal to zero. Polynomial of variable power 2, 1, and 0 terms are there. Any equation having one term in which the power of the variable is a maximum of 2 then it is called a quadratic equation.

Given

The quadratic equation \rm x^(2) + 18 x + 74 = 0.

How to find the value of Q?

If the quadratic equation \rm x^(2) +18x +74=0 is rewritten in the form

\rm (x - p)^2 = Q

Add and subtract 9² in the equation.

\rm x^2 + 18x + 9^2 - 9^2 + 74 =0

We know the formula

\rm (a + b)^2 = a^2 + 2ab + b^2

Then equation will be

\begin{aligned} \rm (x + 9)^2 - 81 + 74 &= 0\n\ \ \ \rm (x + 9)^2 - 7 &= 0\end{aligned}

Add 7 both the sides, then

\rm (x + 9 )^2 = 7

Thus the value of Q is 7.

More about the quadraticequation link is given below.

brainly.com/question/2263981

The value of Q "option C) 7" is correct option.

Step-by-step explanation:

The given quadratic equation:

x^2 - 18x +74=0

To find, the value of Q = ?

x^2 - 18x +74=0

Adding both sides 81, we get

x^2 - 18x +81+74=81

x^2 - 2(x)8 + 9^2 = 81 - 74

Using the algebraic identity,

(a-b)^(2) =a^(2) +b^(2) -2ab

(x-9)^(2) =7 is the form of  (x-p)^2 = Q

Here, P = 9 and Q = 7

Thus, the value of Q "option C) 7" is correct option.

2 times 10 to the eighth power

Answers

2 times 10=20
20 to the 8th power is, 25600000000
2x10 =20.

every "power" is one 0 added to the number, so the answer is 2,000,000,000

Jaclyn used the slope formula to find the slope of the line through the points given in the table.In which step did Jaclyn make an error?

In step 1, she switched the x and y values in point 2.

In step 2, she used the wrong formula for slope.

In step 3, she simplified the slope incorrectly.

Jaclyn did not make an error.

Answers

Answer:

Joselyn did not make an error

Step-by-step explanation:

took the test

Answer:

no error

Step-by-step explanation:

i got it right

the rectangular rug in jody's room is 8 1/2 feet long and 4 feet wide what is the area in square feet of jody's rug

Answers

Multiply the length times the width. 8 1/2 multiplied by 4.
Change it to 17/2 x 4 which equals 68/2. Then simplify it to equal 34 square feet.
The answer will be 34 square feet because 8 1/2 multiplied by 4 is 34.

8 1/2 X 4= (8X4)+(1/2X4)
32 + 2
34 square feet

What is the best way to classify each equation? 22-3x+7x=4(x+5) ,6(2x-3=3(3-5), 6x-14=2(3x-7), 6x+3(x-4)=8(x-3)

Answers

1. 22 - 3x + 7x = 4(x + 5)
   22 - 3x + 7x  = 4x + 20
        +3x  +3x   +3x         
         22 + 10x = 7x + 20
                  -7x   -7x       
           22 + 3x = 20
          -22         -22
                   3x = -2
                    3      3
                     x = -2/3

2. 6(2x - 3) = 3(3 - 5)
    12x - 18 = 3(-2)
    12x - 18 = -6
           +18   +18
           12x = 12
            12     12
               x = 1

3. 6x - 14 = 2(3x - 7)
    6x - 14 =  -3x
    6x - 14 = 2(-7)
    6x - 14 = -14
         +14   +14
           6x = 0
            6     6
             x = 0

4. 6x + 3(x - 4) = 8(x - 3)
    6x + 3x - 12 = 8x - 24
            9x - 12 = 8x - 24
           -8x          -8x       
              x - 12 = -24
                 +12    +12
                     x = -12